The Unaccepted Repudiation: A Thing Still Writ in Water - Brazier, Lauren (Victoria University of Wellington Law Review, 2013)
This article analyses the recent decision of the Supreme Court in Ingram v Patcroft Properties Ltd concerning the legal effect of an unaccepted repudiation. The issue before the Court was whether, and when, a lease had been successfully cancelled by either party. This involved difficult questions of whether there is a "third choice" in the face of a repudiation, the extent to which a party must be ready and willing to perform if it wishes to cancel a contract, and whether the rules of the common law regarding these issues survived the enactment of the Contractual Remedies Act 1979. The article suggests that the Supreme Court did not adequately address these issues. A failure to pinpoint the precise issue in the case gave rise to a confusing judgment that did not fully address the relevant legal principles and their application under the Act. The article discusses those principles, the theoretical issues concerning their application under the Act, and addresses aspects of the judgment in Ingram v Patcroft Properties Ltd that will make the resolution of future cases more difficult.